Clinical Role of ASCT2 (SLC1A5) in KRAS-Mutated Colorectal Cancer - Toda, Kosuke (Int J Mol Sci, 2017)
Mutation in the KRAS gene induces prominent metabolic changes. We have recently reported that KRAS mutations in colorectal cancer (CRC) cause alterations in amino acid metabolism. However, it remains to be investigated which amino acid transporter can be regulated by mutated KRAS in CRC. Here, we performed a screening of amino acid transporters using quantitative reverse-transcription polymerase chain reaction (RT-PCR) and then identified that ASCT2 (SLC1A5) was up-regulated through KRAS signaling. Next, immunohistochemical analysis of 93 primary CRC specimens revealed that there was a significant correlation between KRAS mutational status and ASCT2 expression. In addition, the expression level of ASCT2 was significantly associated with tumor depth and vascular invasion in KRAS-mutant CRC. Notably, significant growth suppression and elevated apoptosis were observed in KRAS-mutant CRC cells upon SLC1A5-knockdown. ASCT2 is generally known to be a glutamine transporter. Interestingly, SLC1A5-knockdown exhibited a more suppressive effect on cell growth than glutamine depletion. Furthermore, SLC1A5-knockdown also resulted in the suppression of cell migration. These results indicated that ASCT2 (SLC1A5) could be a novel therapeutic target against KRAS-mutant CRC.